Digitalization and the Competitive Advantages of Commercial Banks (Eurasian Research Bulletin, 2023)
The article shows the importance of digital banking in the development of interbank competition. With the support of the latest technologies, in order to increase competitiveness, banks are working to identify new business niches, develop customized services, implement innovative strategies, capture new market opportunities and increase profits. An analysis is given of the views of scientists in the field of digital banking, the impact of digital banking on the competitiveness of commercial banks, as well as the main advantages and disadvantages of digitalization.